A Preliminary Study: Protein Extraction Of Migratory Locust (Locusta Migratoria) Via Alkaline Isoelectric Precipitation Method - Asrul Hadi, Nurul Sofea (Universiti Sains Malaysia, 2021)
Unprecedented growth of future human population around the globe seems non capable to overcome high food demand of animal livestock. Increasing in population will coincidentally shrink more livestock farming land. Hence, entomophagy or known as eating insect practice is a promising alternative to circumvent the issue by utilizing the insect protein in worldwide food application. In this preliminary study, protein extraction of oriental migratory locust (Locusta migratoria manilensis) using alkaline isoelectric precipitation was investigated. Firstly, the effect of lipid removal technique to protein content was investigated. Secondly, pH 9 to 13 during solubilisation was applied to obtain the highest protein yield and extraction rate. Initially, the whole dried locust was ground and defatted using ethanol solvent. Defatted locust (DLM) was subjected to alkaline solubilisation for 60 min at 40℃ with addition of 0.25 M NaOH and pH adjustion if necessary.